Application of silver solid amalgam electrodes in electrochemical detection of DNA damage - Svitková, Veronika; Nemčeková, Katarína; Vyskočil, Vlastimil (Analytical and bioanalytical chemistry, 2022)
In this study, a mercury meniscus-modified silver solid amalgam electrode was used for the first time for the detection of UV-induced DNA damage. The integrity of the double-stranded DNA (dsDNA) layer was detected indirectly using the evaluation of the methylene blue reduction within its accumulation into dsDNA after the UV irradiation of the biosensor surface with two different wavelengths (254 nm and 365 nm), monitored by differential pulse voltammetry. Moreover, a simple electrochemical characterization of the biosensor surface was performed using cyclic voltammetry of the redox indicator hexaammineruthenium chloride (RuHex) present in the solution. Electrochemical impedance spectroscopy (EIS) was used in both cases for the verification of results. Individual electrochemical signals depend on the time of biosensor exposure to UV irradiation as well as on the selected wavelengths and are different for both used types of dsDNA (salmon sperm and calf thymus). The highest degradation degree up to 60% was observed using sensitive EIS of methylene blue after 10 min irradiation of the biosensor at 254 nm. The use of RuHex seems to be less sensitive for the detection of dsDNA structural changes, when the degradation degree up to 40% was observed, using EIS at the same conditions.
Keywords: sperma; Electrodes; Humans; Methylene blue; DNA damage; Biosensing Techniques; Amalgam electrode; methylenová modř; elektrody; lidé; biosenzitivní techniky; Silver; Methylene Blue; Electrochemical biosensor; DNA; UV radiation; Male; Electrochemical Techniques; stříbro; Semen; poškození DNA; DNA Damage; mužské pohlaví; elektrochemické techniky